A cross-sectional study on oncology nurses' knowledge and practice of oral mucositis among cancer patients in Jordan - Loai Abu Sharour (Elsevier, 2019)
Objectives: This study was conducted to evaluate oncology nurses' knowledge and compliance with oral mucositis (OM) management guidelines. Methods: A cross-sectional design with a nonparticipant observation approach was utilized. In phase Ⅰ, a cross-sectional convenience sample (n = 140) of oncology nurses completed the knowledge test. In phase Ⅱ, a random sample (n = 20) of oncology nurses from participants in phase Ⅰ was observed during their practice. Results: Fifty-seven (40.7%) of the participants had an unsatisfactory level of knowledge. Most of them had knowledge deficits regarding pathology, OM definition, assessment, scoring, treatment, and patient education and advice. A significant difference existed among nurses with diploma, bachelor, and postgraduate degrees as determined by one-way ANOVA (P = 0.001). There were no significant difference between average scores of male and female nurses were higher than those of nurses (P = 0.45). No significant difference was observed among knowledge scores of nurses with different job titles (P = 0.51). The average score of male nurses in terms of skill performance was higher than that of female nurses (29.20 ± 2.10 vs 27.10 ± 1.80) without statistical significance. Conclusion: The knowledge and compliance with OM management guidelines among Jordanian oncology nurses need to be improved. National OM prevention and management guidelines are adopted in Jordan. Continuing education and training are also recommended. Keywords: Jordan, Knowledge, Medical oncology, Nurses, Questionnaire, Stomatitis